2022
DOI: 10.15421/022228
|View full text |Cite
|
Sign up to set email alerts
|

Post-slaughter indicators of meat productivity and chemical composition of the muscular tissues of bulls receiving corrective diet with protein-vitamin premix

Abstract: The problem of increasing the production of beef to provide the population with domestically-produced meat is mainly being solved by selective breeding of dairy and combined breeds. Therefore, there is a need for the development and introduction of complex measures to increase meat productivity of young cattle, especially regarding the completeness of diet and optimal content of mineral elements in it. The study was conducted on bulls of the Ukrainian Black-Spotted Dairy breed starting from the age of 6 up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…The main objective of modern animal farming is achieving maximum productivity through realization of the genetic potential and survival of the populations, decrease in production costs, and production of highquality meat. Studies by Yaremchuk et al (2022) and Farionik et al (2023) confirmed the importance of correcting the animals' diets with mineral premixes for more intensive growth and enhancement of meat quality. One of the key tendencies in the development of poultry farming has been not only continuous improvement of meatiness, but also improvement of the quality characteristics of the produced meat.…”
Section: Discussionmentioning
confidence: 91%
“…The main objective of modern animal farming is achieving maximum productivity through realization of the genetic potential and survival of the populations, decrease in production costs, and production of highquality meat. Studies by Yaremchuk et al (2022) and Farionik et al (2023) confirmed the importance of correcting the animals' diets with mineral premixes for more intensive growth and enhancement of meat quality. One of the key tendencies in the development of poultry farming has been not only continuous improvement of meatiness, but also improvement of the quality characteristics of the produced meat.…”
Section: Discussionmentioning
confidence: 91%
“…In the subsequent periods of rearing, the greatest advantage in this indicator was found in chickens that were supplemented with a copper chelate complex. The increase in the average daily live weight gain was 10.7% during days [15][16][17][18][19][20][21][22]19.2% (p<0.001) during days [22][23][24][25][26][27][28][29]7.5% (p<0.01) during days 29-36, and 18.8% (p<0.001) in the final period of rearing. The supplementation of the diet also resulted in lower scores than in the third group, but still higher than in the first control group.…”
Section: Resultsmentioning
confidence: 99%
“…Ефективність підвищення продуктивності сільськогосподарської птиці залежить від того, наскільки технології виробництва дають змогу реалізувати її генетичний потенціал. Головним фактором реалізацій генетичного потенціалу птиці є згодовування повноцінних комбікормів та білково-вітамінних добавок (Sobolev et al, 2019;Shcherbatyy & Slivinska, 2021;Yaremchuk et al, 2022;.…”
Section: вступunclassified